Ecuador Public Finance Review : Phase Two - World Bank (World Bank, Washington, DC, 2019)
The Ecuador public finance review (PFR) series responded to a request from the Ecuadorian Ministry of Economy and Finance (MEF) to assess the efficiency and effectiveness of public spending. The PFR series offers a combination of analysis, capacity building, and options for reform in selected areas and sectors of the budget to achieve efficiency gains and fiscal savings, while improving (or at least preserving) equity. The PFR-phase two complements and deepens the analysis and capacity building initiated under phase one. Phase two also includes an analysis of the efficiency of public spending in education. As in phase one, phase two was accompanied by a number of technical assistances related to the areas covered by the study, including: an Ecuador specific forecasting model, BOOST database for Ecuador, public financial management, impacts of tax on capital outflows, public wage bill forecast and simulation, and efficiency of spending.